Tropical wetland persistence through the Anthropocene: Multiproxy reconstruction of environmental change in a Maya agroecosystem. (June 2021) - Krause, Samantha; Beach, Timothy P.; Luzzadder-Beach, Sheryl; Cook, Duncan; Bozarth, Steven R.; Valdez, Fred; Guderjan, Thomas H.
Abstract: Wetlands epitomize all forms of the proposed Anthropocene era because they record both past and recent human environmental interaction and because of their abundant resources. This is especially true for tropical wetlands, and a growing body of research demonstrates their important connections with past and Indigenous societies. Maya culture, for example, provides an extraordinary example of wetland use in the "Early Anthropocene". Through excavations and lidar survey, we demonstrate that ancient Maya farmers managed riparian wetlands in northwestern Belize to a much greater spatial extent than previous estimates. This paper provides new evidence from soil geomorphic and palaeoecological excavations within the Birds of Paradise wetland in Belize. We focus on the timing, extent, and intensity of human management as well as soil pedogenesis and ecological changes over the last c. 2000 years. Bayesian modelling of radiocarbon dates show the transformation of the wetland from a natural to an agricultural system, starting as early as c. 2100 BP. The Maya were constructing berms on the margin of the wetland by c. 1600 BP, and widespread clearing and canal construction began by c. 1350-1290 BP. These periods coincide with population growth and decline and urban construction and abandonment in this region. This clearing, farming, and channelization ended as late as c. 690-620 BP based on canal sedimentation, pollen evidence reflecting tropical forest replacing cultivars like maize, and soil carbon isotope ratios that reflect C4 plants like maize shifting to more mixed and C3 plants. We demonstrate the complexity and scale of human engineering and modification of soil and water resources, provide a new chronology for ancient wetland use, and present new evidence for the farming of economic plants as well as the succession of tropical wetlands after intensive anthropogenic manipulation ceased.